Effects of Impoundment on Macroinvertebrate Community Assemblages in Upland Streams. (6th June 2014) - Gillespie, B. R.; Brown, L. E.; Kay, P.
Abstract Approximately 15% of the world's river flow is regulated, but evidence for the impacts of regulation on macroinvertebrate communities remains contradictory. Sound understanding of this topic is now required to meet legislative targets (e.g. EU Water Framework Directive good ecological potential). In the UK, research has either been undertaken at large (national) or small (reach) scales, and typically, researchers have made comparisons between sites classed simply as either regulated or unregulated. We present an alternative, medium (regional) scale study and contrast three methods of defining the extent to which a site is regulated (ER): (i) regulated or unregulated (ERLOW); (ii) fully‐regulated, semi‐regulated or unregulated (ERMED); and (iii) a continuous score reflecting the relative regulated and unregulated river influence on a site (ERHIGH). The potential for highlighting the impacts of regulation of two recently developed pressure‐specific biotic indices [Lotic Invertebrate index for Flow Evaluation (LIFE) and Proportion of Sediment‐sensitive Invertebrates] is also assessed. We found that (i) regulation was associated with reduced relative abundance of Coleoptera and Ephemeroptera and enhanced relative abundance of Trichoptera, Chironomidae and Oligochaeta; (ii) Potamopyrgus antipodarum and Amphinemura sulcicollis were both positively associated with regulation; this observation is novel for the UK; (iii) ERHIGH was superior to both ERLOW and MED as a means of detecting an impact; and (iv) of all indices tested, only LIFE was significantly associated with regulation. The use of LIFE and ERHIGH should be tested further to understand the extent to which they can provide clearer insights into the effects of river regulation on macroinvertebrate communities. Copyright © 2014 John Wiley & Sons, Ltd.